Sosialisasi Fitur Pendaftaran Online Menggunakan Aplikasi Mobile JKN untuk Pelayanan Rawat Jalan - Ibrahim, Mochammad Malik; Eka Yusmanisari; Wulan Ayu P; Azka Himatul U; Dhe Shinta M; Ghina Rahmania; Yani Nurul F; Zuhrotul Miladiyah; Roby Febriansyah; Ria Irmanda P. M; Rizkynieta Dwi I; Wasilah Munawaroh; Cahya Arum Y; Dwi Ariska K.D; M. Arika Abu B (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Mobile JKN provides various features to facilitate its users, one of which is online service registration. However, many people do not know about the benefits of utilizing mobile JKN. Only 0.05% of patients at Menur Mental Hospital registered using mobile JKN. The purpose of this community service is to introduce the JKN mobile application to patients or patients' families. The method of community service carried out is socialization, data collection is done by interview and questionnaire assistance. The target of this socialization activity is the patient or patient's family, the informants also contribute, namely medical record officers and PKRS officers. After the material was delivered, the respondents were asked to practice it directly. This community service activity runs smoothly, it is expected that there will be an increase in patients who register themselves using mobile JKN so that it can succeed the JKN program in Surabaya City.